A novel animal model of neuropathic corneal pain–the ciliary nerve constriction model - Seyed-Razavi, Yashar; Kenyon, Brendan M.; Qiu, Fangfang; Harris, Deshea L.; Hamrah, Pedram (Frontiers in Neuroscience, 2023)
Neuropathic pain arises as a result of peripheral nerve injury or altered pain processing within the central nervous system. When this phenomenon affects the cornea, it is referred to as neuropathic corneal pain (NCP), resulting in pain, hyperalgesia, burning, and photoallodynia, severely affecting patients' quality of life. To date there is no suitable animal model for the study of NCP. Herein, we developed an NCP model by constriction of the long ciliary nerves innervating the eye. Mice underwent ciliary nerve constriction (CNC) or sham procedures. Safety was determined by corneal fluorescein staining to assess ocular surface damage, whereas Cochet-Bonnet esthesiometry and confocal microscopy assessed the function and structure of corneal nerves, respectively. Efficacy was assessed by paw wipe responses within 30 seconds of applying hyperosmolar (5M) saline at days 3, 7, 10, and 14 post-constriction. CNC resulted in significantly increased response to hyperosmolar This is a provisional file, not the final typeset article saline between groups (p<0.0001), demonstrating hyperalgesia and induction of neuropathic pain.Further, animals that underwent CNC had increased anxiety-like behavior in an open field test compared to controls at the 14-and 21-day time-points (p<0.05). In contrast, CNC did not result in increased corneal fluorescein staining or decreased sensation as compared to sham controls.Additionally, confocal microscopy of corneal whole-mounts revealed that constriction resulted in a slight reduction in corneal nerve density (p<0.05), compared to naïve and sham groups. Taken together, these results indicate that the CNC model induces a pure NCP phenotype and may be a useful model for the study of NCP.